Praktik Kuasa Platform Media Sosial Di Balik Kecanduan Media Sosial Bagi Remaja - Koli, Nicodemus (Indonesian Character Journal, 2024)
In the present time, browsing through social media via smartphones is one of the top reasons for using the internet. Through social media, everyone has a space to express their thoughts, feelings, actions, and attitudes easily and quickly. The personality traits, interests, and preferences of every individual are readable, peeked into, and monitored. Every symbol, advertisement, information, and product promotion that aligns with the user's desires and character is continuously presented by social media platforms. Experts who have careers and strategic positions, as well as being the creators of various captivating control features in companies like Google and Facebook, along with scientists, discuss this issue clearly in a series of interviews that are later presented in the documentary film "The Social Dilemma." The analysis of this documentary film is conducted using a discourse analysis approach within the framework of Michel Foucault's thinking on power relations. From this, it can be understood that companies with platforms such as Google, Facebook, Twitter, Silicon Valley, Snap-chat, Instagram, and YouTube practice power as strategic relations. The development of technology in the control systems owned by companies and social media platforms can manipulate psychological aspects, thus conditioning social media users to appear active. Within the framework of power discourse as a strategic relation, social media users are conditioned within the surveillance capitalism. As a result, changes in habits, ways of thinking, and user behavior are controlled. Di zaman sekarang, menjelajahi media sosial melalui ponsel pintar adalah salah satu alasan utama penggunaan internet. Melalui media sosial, setiap orang memiliki ruang untuk mengungkapkan pemikiran, perasaan, tindakan, dan sikap mereka dengan mudah dan cepat. Sifat kepribadian, minat, dan preferensi setiap individu dapat dibaca, diselidiki, dan dimonitor. Setiap simbol, iklan, informasi, dan promosi produk yang sejalan dengan keinginan dan karakter pengguna terus-menerus disajikan oleh platform media sosial. Para ahli yang memiliki karier dan posisi strategis, serta menjadi pencipta berbagai fitur pengendalian yang menarik dalam perusahaan seperti Google dan Facebook, bersama dengan para ilmuwan, membahas isu ini secara jelas dalam serangkaian wawancara yang kemudian disajikan dalam film dokumenter "The Social Dilemma." Analisis film dokumenter ini dilakukan dengan pendekatan analisis wacana dalam kerangka pemikiran Michel Foucault tentang hubungan kekuasaan. Dari ini, dapat dipahami bahwa perusahaan dengan platform seperti Google, Facebook, Twitter, Silicon Valley, Snapchat, Instagram, dan YouTube menjalankan kekuasaan sebagai hubungan strategis. Perkembangan teknologi dalam sistem pengendalian yang dimiliki oleh perusahaan dan platform media sosial dapat memanipulasi aspek psikologis, sehingga mengkondisikan pengguna media sosial untuk tampil aktif. Dalam kerangka wacana kekuasaan sebagai hubungan strategis, pengguna media sosial dikondisikan dalam kapitalisme surveilans. Akibatnya, perubahan dalam kebiasaan, cara berpikir, dan perilaku pengguna dikendalikan.